Preparation and physicochemical properties of zeolitic imidazolate framework-8 (ZIF-8)/rice husk derived graphene (GRHA) nanohybrid composites. Issue 5 (January 2020) - Arifin, N F T; Yusof, N; Nordin, N A H M; Raimi, N I C; Jaafar, J; Ismail, A F; Aziz, F; Salleh, W N W
Abstract: This paper proposes an improve nanohybrid composites of Zeolitic Imidazolate Framework-8 (ZIF-8)/Rice husk Derived Graphene (GRHA). The main goal of this work is to prepare the nanohybrid composites with high surface area and enhanced porosity. The composite is prepared via aqueous room temperature method which is simple and fast. Based on Fourier transform Infrared (FTIR) and X-ray Diffraction (XRD) analysis, it shows that the produced ZIF- 8 is in sodalite (SOD) structure while GRHA is in amorphous due to the presence of multilayer graphene. Raman analysis shows that the prepared GRHA has a high degree of graphitization. The BET specific surface area (BETSSA ) is found to increase up to three times higher (1632.10 m 2 /g) as compared to pristine GRHA (518.11 m 2 /g) and ZIF-8 (687.32 m 2 /g) respectively. Therefore, it is envisaged that this composite can be very useful for hydrogen storage.